The usage of electroimpedancemetry in the diagnostics of acute sinusitis - A. V. Davidov (Бюллетень сибирской медицины)
For the first time in the rhinological practice the methods of evaluation of the functional state of tissues of nasal cavity that were based on registration of their electrical features-electrical resistance (impedance) and potencial were worked out. In the comparative aspect there were researched the active and the passive electrical features of the tissues of nasal cavity which healthy people and those whose disease is acute sinusitis, have. For the first time the dynamic of electrical features was studied and the most informative electrical rates for the initial diagnostic of acute sinusitis and for evaluation of the effectiveness of appointed treatment were revealed. As a result of researches a new way of noninvasive diagnostic of inflammatory diseases of paranasal sinus was worked out, approved and inserted in practice. (Patent № 2157094, 10.10.2000 «The way of diagnostic of inflammatory diseases of paranasal sinus»). The suggested way is simple, reliable; it has high credibility value of revealing the pathologies of paranasal sinus and evaluation of its dynamic. This method may be recommended for the wide usage in hospitals and clinics for diagnostic of acute sinusitis and evaluation of effectiveness of treatment.